THE IMPACT OF WORK DISCIPLINE, WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN MARINE AND FISHERY SERVICES SOUTH ACEH DISTRICT - saipul bahri; Muzakir Muzakir (universitas teuku umar, 2022)
This study aims to see the effect of work discipline and work environment on employee performance at the Department of Maritime Affairs and Fisheries, South Aceh Regency. This research is quantitative descriptive. The research population is all civil servants and non-civil servants who work in the service, totaling 50 people. Questionnaires were distributed to all respondents with 33 respondents who returned the questionnaire which were then used as research samples. The results showed that partially work discipline had a positive and significant effect on employee performance. The work environment has a positive but not significant effect on employee performance at the Department of Marine Affairs and Fisheries, South Aceh Regency. Simultaneously, the variables of work discipline and work environment have a positive and significant influence on the performance of employees at the Department of Maritime Affairs and Fisheries, South Aceh Regency. Overall, work discipline and work environment variables can only explain employee performance variables as much as 33%, while 77% percent are explained by other factors not mentioned in the study. Keywords: Work Discipline, Employee Performance, Work Environment, Motivation.